Answer:
C is the polynomial but idk if it's correct or not
Answer:
x² - 3x + 5 - [24÷(x+3)]
Step-by-step explanation:
1. Expand (x³ + 2x - 6x - 9)
= x³ - 4x - 9
2. Divide [x³ - 4x - 9 by x+3]
= x² + [(-3x^2-4x-9) ÷ (x+3)]
3. Divide [(-3x^2-4x-9) by (x+3)]
= -3x + [(5x-9) ÷ (x+3)]
x² - 3x + [(5x-9) ÷ (x+3)]
4. Divide [(5x-9) ÷ (x+3)]
= 5 + [(-24) ÷ (x+3)]
x² - 3x + 5 + [(-24) ÷ (x+3)]
= x² - 3x + 5 - [24 ÷ (x+3)]
Answer:
1354
Step-by-step explanation:
DO IT IT'S EASY WITH A CALCULATOR !!!!!!
Answer:
Go catipiller
Step-by-step explanation: